The IBC Amendments to Usher in the CrossBorder Insolvency Resolution - Madupalli, Ravi; Rao, Ch. Lakshmana (International Journal of Psychosocial Rehabilitation, 2024)
If we speak globally, the cross-border insolvency laws have been based on one country which is providing the assistance to the other country in taking full control of the assets and also the eventual disposition of such assets of the debtor company. Such type of aims could be easily achieved by the mutual recognition of each country’s insolvency regime. For instance, the UK has recognized the insolvency provisions of certain Commonwealth jurisdictions and also the courts in the UK have been bound to assist the courts in all such Commonwealth jurisdictions. India has not been one of the jurisdictions that would qualify for the benefit under this route. The European Union (EU) is also one of the most effective cross-border regimes where, under the Insolvency Regulation 1346 / 2000, the country where the proceedings have been initiated against the debtor and the Centre of Main Interests has been located in such a country, the laws of that country would automatically take the priority and have the same effect in all the other member states and would also govern all such issues except those which have been specifically excluded. With regard to the cross-border insolvency laws in India, under the Companies Act, 1956, a court could definitely order the winding up of an unregistered company, which had included a foreign company. However, if an Indian company with the assets abroad was sought to be wound up, there was no specific statutory process for conducting the proceedings. It was also based on the mutual recognition of the foreign decrees as in the Code of the Civil Procedure, 1908, in India. Further, the Foreign creditors could also independently proceed against the assets of the company as located under the foreign jurisdiction. In the absence of such a recognition, it is very much difficult for any liquidator to gather the information on the different assets and enforce the disposition of all the foreign assets in a liquidation process.